CEREBRAL AUTOSOMAL DOMINANT ARTERIOPATHY WITH SUBCORTICAL INFARCTIONS AND LEUKOENCEPHALOPATHY. CADASIL SYNDROME (DESCRIPTION OF A CLINICAL CASE) - Елена Алексеевна Полукарова; Наталья Васильевна Рогожникова; Ирина Николаевна Шарапова; Валерия Викторовна Пиминова (Медицина в Кузбассе)
A clinical case of a 47-year-old patient with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy is presented. It is known that the patient has a family history, her brother was diagnosed with CADASIL syndrome on the basis of autopsy, and the patient herself had CADASIL syndrome verified by genotyping in 2020. Over the past three years, recurrent strokes have been observed in the right and left SMA basins, with worsening clinical symptoms in the form of increased hemiparesis, the appearance of pseudobulbar and neurodynamic disorders. A special feature of the case is the absence of clinical symptoms outside of acute cerebral circulatory disorders, the symptoms of which are completely relieved.